A binary metal organic framework derived hierarchical hollow Ni3S2/Co9S8/N-doped carbon composite with superior sodium storage performance. Issue 23 (22nd March 2017) - Liu, Xinye; Zou, Feng; Liu, Kewei; Qiang, Zhe; Taubert, Clinton J.; Ustriyana, Putu; Vogt, Bryan D.; Zhu, Yu
Abstract : The carbonization and sulfurization of a hierarchical hollow MOF leads to anode materials with exceptional performance in Na + batteries with high cycle stability and rate performance. Abstract : A binary Ni/Co metal organic framework (Ni–Co-MOF) with a hollow-sphere structure that is decorated with cone-shaped protrusions was prepared via a facile solvothermal reaction. Carbonization and sulfurization of the Ni–Co-MOF produced a Ni3 S2 /Co9 S8 /N-doped carbon composite that retained the hierarchical structure. The final composite material presents exceptional electrochemical performance when used as an anode in sodium-ion batteries. A reversible specific capacity of 419.9 mA h g −1 at a current density of 0.1 A g −1 was achieved after 100 cycles, with an exceptional capacity retention of 98.6%. Furthermore, superior rate capability was also demonstrated: an average capacity of 323.2 mA h g −1 at a current density of 2 A g −1 can be achieved. This exceptional performance can be attributed to the unique nano-architecture derived from the MOF precursor, as the resultant material possesses an ideal profile for an excellent anode material: ultrafine Ni3 S2 and Co9 S8 particles (∼7 nm), a hollow, porous structure, and an ultrathin N-doped carbon coating.